The rights of employees in private sector to leave entitlement in Malaysia / Nadia Mohd Izhar and Aidzri Imran Ibrahim. - Mohd Izhar, Nadia; Ibrahim, Aidzri Imran (Faculty of Law, 2007)
This research was conducted to determine whether the employees are aware of their rights in leave entitlement include public holiday, rest day, annual leave, sick leave, and maternity leave. Besides that, it is to determine whether the employers follow the laws and rules as provided in the statutes. This topic was chosen because it has never been brought up for discussion despite the fact that this problem is getting serious the reasons why it has never been brought up for discussion was because no complaint have been made by anyone besides there is no responsible bodies to look after this matter. An action can only be taken if there is complaint made. The matter of leaves entitlement seems not to be so serious on the surface however; impliedly it plays a major role employment field. For example if an employee does not get enough rest due to shortage of workers and he has to work continuously without rest, this might affect his working ability and definitely will affect the company too. Another situation is if an employee's application for leave is rejected and the wages paid to him is an ordinary rate, this can also affect his working ability when he is not enjoying the work given thus can affect the company's reputation. The aim of this research is to create awareness among the employers and employees as to give a serious view on this matter. Therefore, this issue needs more discussion and explanation for future benefits.